78.8k views
4 votes
Can I get some help been trying to figure this question on but don’t seem to get it.

Can I get some help been trying to figure this question on but don’t seem to get it-example-1
User Prohit
by
5.8k points

1 Answer

4 votes

Answer:

  • left box: 25/36
  • right box: 5/6

Explanation:

If you square the binomial (x -a), you get ...

(x -a)² = x² -2ax +a²

Comparing this to your equation, you find that ...

-2a = -5/3 . . . . . . the x-coefficient

a = (1/2)(5/3) = 5/6

So, the number in the right box is 5/6, and the number in the left box is its square, (5/6)² = 25/36.

Filling these in, the equation reads:

x² -5/3x +25/36 = (x -5/6)²

__

That is, the constant in the squared binomial is half the x-coefficient.

User ZarathustrA
by
6.3k points